Pulling rank - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Sirat Seied Yesut, an irrigation specialist working in the Amhara region of Ethiopia writes about the way CTA supports and organises seminars. 'Why doesn't CTA consider widening the professional know-how of low-ranking experts like me, who can...